In vivo phase II-enzymes inducers, as potential chemopreventive agents, based on the chalcone and furoxan skeletons. Issue 8 (15th April 2016) - Cabrera, Mauricio; Mastandrea, Ignacio; Otero, Gabriel; Cerecetto, Hugo; González, Mercedes
Graphical abstract: Abstract: Cancer chemoprevention involves prevention/delay/reverse of the carcinogenic process through administration of cancer chemopreventive agents (CCA). Compounds which are able to induce detoxification-enzymes, especially monofunctional phase II enzymes, have become in excellent approaches for new CCA. Herein, we report the synthesis of new furoxanyl chalcone-like hybrid compounds as CCA. In vitro studies showed that phenylfuroxanyl derivatives6 and9 displayed the best activities being9 the greatest monofunctional-inducer. Additionally, compounds were non-mutagenic against TA98 Salmonella typhimurium strain (Ames test) and could be used in the prevention of the progression of pre-malignant lesions for their cytotoxic activity against tumoral cells. In vivo proof of concept showed increment on phase II-enzymes activities in liver, colon and mammary gland having derivative9 the best induction profiles. We probed Nrf2 nuclear translocation is operative for both compounds allowing to exert protective effects via expression of downstream phase-II enzymes.